Water quality and heavy metal prospective at Pengkalan Chepa River Basin, Kelantan - Maliki @ Abdullah, Mohd Saifuddin (2020)
Malaysia is a rapidly growing developing country since independence in 1957, from a rural economy to an export-based manufacturing economy. In 2017, 54% of rivers found polluted due to anthropogenic activities. Pengkalan Chepa River Basin (PCRB) is located in a developing area in Kota Bharu district. This study was to determine the water quality status at PCRB based on Water Quality Index (WQI) and heavy metal concentration in river water. Water samples were collected from 11 stations along the river and analyzed using YSI 556 MPS for in-situ test and laboratories analyzed for ex-situ test. Meanwhile, heavy metal concentrations were analyzed using AAS. Water sampling was carried out starting from November 2018 until Jun 2019, covering wet and dry seasons. The finding shows total median value for water quality parameters; DO (2.72 mg/L), BOD (6.42 mg/L), COD (33.5 mg/L), NH3-N (1.02 mg/L), TSS (27 mg/L) and pH (6.97). According to WQI, PCRB was classified under Class III for both seasons and considered as slightly polluted. Concentration of heavy metals in water followed the order, Fe > Cr > Zn > Cu > Cd. Almost all the heavy metals were found within the permitted level by the National Drinking Water Quality Standard (NDWQS) except for Cd. Kruskal Walis test shows a significant difference between parameters (DO, BOD, COD, NH3-N and pH) and sampling locations (ρ < 0.05). Based on this study, it can be concluded that the water quality of PCRB is polluted based on DO, BOD, COD, NH3-N and Cd aspects.